Explant analysis and implant registries are both needed to further improve patient safety - Morlock, Michael; Gomez-Barrena, Enrique; Wirtz, Dieter Christian; Hart, Alister; Kretzer, Jan Philippe (EFORT open reviews, 2022)
In the early days of total joint replacement, implant fracture, material problems and wear presented major problems for the long-term success of the operation. Today, failures directly related to the implant comprise only 2–3% of the reasons for revision surgeries, which is a result of the material and design improvements in combination with the standardization of pre-clinical testing methods and the post-market surveillance required by the legal regulation. Arthroplasty registers are very effective tools to document the long-term clinical performance of implants and implantation techniques such as fixation methods in combination with patient characteristics. Revisions due to implant failure are initially not reflected by the registries due to their small number. Explant analysis including patient, clinical and imaging documentation is crucial to identify failure mechanisms early enough to prevent massive failures detectable in the registries. In the past, early reaction was not always successful, since explant analysis studies have either been performed late or the results did not trigger preventive measures until clinical failures affected a substantial number of patients. The identification of implant-related problems is only possible if all failures are reported and related to the number of implantations. A system that analyses all explants from revisions attributed to implant failure is mandatory to reduce failures, allowing improvement of risk assessment in the regulatory process.